The Effect of the Federal Reserve's Tapering Announcements on Emerging Markets - Vikram Rai; Lena Suchanek (Bank of Canada, 2014)
The Federal Reserve's quantitative easing (QE) program has been accompanied by a flow of funds into emerging-market economies (EMEs) in search of higher returns. When Federal Reserve officials first mentioned an eventual slowdown and end of purchases under the central bank's QE program in May and June 2013, foreign investors started to withdraw some of these funds, leading to capital outflows, a drop in EME currencies and stock markets, and a rise in bond yields. Using an event-study approach, this paper estimates the impact of "Fed tapering" on EME financial markets and capital flows for 19 EMEs. Results suggest that EMEs with strong fundamentals (e.g., stronger growth and current account position, lower debt, and higher growth in business confidence and productivity), saw more favourable responses to Fed communications on tapering. Capital account openness initially played a role as well, but diminished in importance in subsequent tapering announcements.
Keywords: C33; E58; F32; G14; 330; International financial markets; Transmission of monetary policy; International topics